Exploring the role of the complement system, endothelial injury, and microRNAs in thrombotic microangiopathy after kidney transplantation - Aleš Rigler, Andreja; Večerić-Haler, Željka; Arnol, Miha; Perše, Martina; Boštjančič, Emanuela; Pleško, Jerica; Simčič, Saša; Kojc, Nika (Journal of international medical research, 2020)
Objective We investigated whether the recipient’s complement system function, kidney graft endothelial ultrastructural injury, and microRNA (miRNA) expression before transplantation may be associated with the risk of posttransplant de novo thrombotic microangiopathy (TMA). Methods Complement system function assessment, histological and ultrastructural examination of preimplantation and kidney graft biopsies, and microRNA assessment were performed on kidney transplant recipients (KTRs) with de novo TMA. Results On the basis of the clinical course, histological findings, and miRNA patterns, the following two de novo TMA phenotypes were observed: a self-limiting disease that was localized to the kidney graft and a systemic disease that progressed to graft failure without timely treatment. Decreased alternative complement pathway activity and ultrastructural endothelial injury before transplantation were confirmed in all five KTRs and four of five KTRs, respectively, but they did not correlate with de novo TMA severity. Conclusions Alternative complement pathway abnormalities in KTRs and endothelial ultrastructural injury on preimplantation biopsy might be associated with de novo posttransplant TMA, although they did not predict posttransplant TMA severity (localized vs. systemic). The specific miRNA expression patterns in preimplantation kidney graft biopsies demonstrated a borderline statistically significant difference and might provide more accurate information on posttransplant TMA severity.